The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-28648-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative degradation of polyamines by serum supplement causes cytotoxicity on cultured cells

Abstract: Serum is a common supplement for cell culture due to it containing the essential active components for the growth and maintenance of cells. However, the knowledges of the active components in serum are incomplete. Apart from the direct influence of serum components on cultured cells, the reaction of serum components with tested drugs cannot be ignored, which usually results in the false conclusion on the activity of the tested drugs. Here we report the toxicity effect of polyamines (spermidine and spermine) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 41 publications
(43 reference statements)
4
24
0
Order By: Relevance
“…One of these factors in in vitro studies could be the use of animal serum in the cell culture medium, which contains amino oxidases that can oxidize exogenously administrated polyamines and generate ROS, resulting in cell toxicity independently of the action of the polyamine itself. Interestingly, a recent work demonstrated that in the presence of human serum, polyamine administration to the culture medium does not increase ROS production and does not affect cell viability as in the case of the same experiment in presence of either bovine or horse serum ( 45 ). Importantly, studies showing a polyamine-dependent cell toxicity in human cell lines in presence of significant amounts of bovine/horse serum should be reevaluated with human serum to corroborate that toxicity could be due to the production of oxidized polyamine-derived products by the action of serum polyamine oxidases and not to a toxic effect of the polyamines per se .…”
Section: Polyamine Functionsmentioning
confidence: 89%
“…One of these factors in in vitro studies could be the use of animal serum in the cell culture medium, which contains amino oxidases that can oxidize exogenously administrated polyamines and generate ROS, resulting in cell toxicity independently of the action of the polyamine itself. Interestingly, a recent work demonstrated that in the presence of human serum, polyamine administration to the culture medium does not increase ROS production and does not affect cell viability as in the case of the same experiment in presence of either bovine or horse serum ( 45 ). Importantly, studies showing a polyamine-dependent cell toxicity in human cell lines in presence of significant amounts of bovine/horse serum should be reevaluated with human serum to corroborate that toxicity could be due to the production of oxidized polyamine-derived products by the action of serum polyamine oxidases and not to a toxic effect of the polyamines per se .…”
Section: Polyamine Functionsmentioning
confidence: 89%
“…For determination of cytotoxicity, cells at a final density of 5 × 10 5 cells/ml in serum-free RPMI-1640 media were treated with one or more drugs for 24 h for each cell line. The sole exception was cytarabine, where LD50 was determined over 48 h, with a media change and fresh cytarabine added at 24 h. Drug cytotoxicity was determined in serum-free media to prevent reaction of serum components with drugs, as this has been shown to compromise the test results on cytotoxicity 12 . Survival rates were assessed using exclusion of 0.4% Trypan Blue (Gibco) using a Countess TM II FL (ThermoFisher) automated cell counter.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have since concluded that adding Spd or Spm to mammalian cells in the presence of bovine serum results in extracellular oxidation of the PA and growth inhibition due to the oxidation products, not the exogenous PA (63-66). Studies testing the inhibitory effects of Spm, Spd, their aldehyde reac-tion products (which can convert to acrolein), and H 2 O 2 in mammalian cell lines have indicated major roles for acrolein and H 2 O 2 in the cytotoxic responses (51,(67)(68)(69), and in most systems, treatment with aldehyde dehydrogenase inhibitors and catalase together yielded protection from cytotoxicity (70,71). Therefore, caution must be used when interpreting results involving PA treatment of cells in culture, particularly with regard to cellular processes involving ROS, such as autophagy.…”
Section: Polyamine Catabolism As a Source Of Rosmentioning
confidence: 99%